A trial to allow motorcycles on bus lanes in Tel-Aviv: an assessment of mobility and safety impacts - Victoria Gitelman; Roby Carmel; Anna Korchatov (Transactions on Transport Sciences, 2022)
While motorcycles or powered two-wheelers (PTWs) provide mobility benefits in dense urban areas, their riders are exposed to a high risk of injury. Bus lane use by PTWs is suggested in international practice as a measure for improving PTW safety and mobility although examinations of its impacts are rare, with results reported mostly in the United Kingdom. Based on the literature, it was anticipated that the measure would increase the use of bus lanes by PTWs and keeping to their travel lanes, thus improving PTW mobility and reducing conflicts with other vehicles. However, concerns were raised regarding possible disturbances to bus traffic while the safety impacts of the measure are unclear. In Israel, a trial on the use of bus lanes by PTWs was introduced in Tel-Aviv, on two major traffic routes, and was accompanied by an evaluation study. The study aimed to examine the mobility and safety impacts of the measure, by comparing PTW behaviors and accident numbers, during the trial as opposed to the before period. The study observations were collected by means of video-recordings on road sections, traffic cameras at junctions, and mobile cameras attached to helmets in a group of PTW volunteers. The findings showed that during the trial, the rate of PTWs using bus lanes increased by 4-5% when traffic was flowing, and by 6-8% when traffic was congested, but PTWs continued to be observed on other traffic lanes. When travelling through a road segment, most PTWs kept to their lane, but a consistent change in this behavior was not found. During the trial, the amount and severity of conflicts between PTWs and other vehicles did not increase, and the passing times of buses and PTWs along the routes did not change. Mixed trends were observed in both total and PTW-involved accidents, with no significant change. Overall, allowing PTWs on the bus lanes in Tel-Aviv resulted in slight improvements in PTW mobility, without impairing bus travel times or road safety. The absence of substantial behavior changes during the trial indicated that the new measure actually "regulated" the situation that was previously present in traffic.